2023
DOI: 10.7759/cureus.38627
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Biomarkers in Delirium Superimposed on Dementia (DSD) and Their Clinical Application to Personalized Treatment and Management

Abstract: Delirium superimposed on dementia (DSD) occurs when patients with pre-existing dementia develop delirium. This complication causes patients to become impaired, posing safety concerns for both hospital staff and patients. Furthermore, there is an increased risk of worsening functional disability and death. Despite medical advances, DSD provides both diagnostic and therapeutic challenges to providers. Identifying at-risk patients and providing personalized medicine and patient care can decrease disease burden in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Malewska et al indicated higher BDNF levels after the presence of AWS with DTs than before AWS [ 28 ]. The findings suggest that BDNF might be a candidate for personalized medicine-based detection of delirium [ 118 ]. Moreover, Huang et al suggested that chronic drinking leads to decreased BDNF levels, and patients with more deficient BDNF expression are prone to the development of DTs [ 119 ].…”
Section: Resultsmentioning
confidence: 99%
“…Malewska et al indicated higher BDNF levels after the presence of AWS with DTs than before AWS [ 28 ]. The findings suggest that BDNF might be a candidate for personalized medicine-based detection of delirium [ 118 ]. Moreover, Huang et al suggested that chronic drinking leads to decreased BDNF levels, and patients with more deficient BDNF expression are prone to the development of DTs [ 119 ].…”
Section: Resultsmentioning
confidence: 99%
“…In our study, the effect estimate of IVW (OR 1.32, 95% CI 1.13–1.54) demonstrates that AD is indeed a risk factor for delirium, which aligns with previous research demonstrating that dementia and recognition decline are independent risk factors for delirium [ 31 , 32 ]. Although the exact mechanisms of delirium are not completely understood, it is believed to be a multifactorial process that can result in brain dysfunction, often involving abnormal nerve transmission and neuroinflammation [ 10 , 33 , 34 ]. Patients with dementia and pre-existing neurodegeneration may be more prone to neuroinflammatory cytokines, and trigger greater oxidative stress during surgery, pain or other stressful situations, potentially increasing the risk of delirium.…”
Section: Discussionmentioning
confidence: 99%
“…In order to early recognize vulnerable patients with high risk for postoperative delirium development, a brief evaluation of the cardiopulmonary status, prescribed and overthe-counter medication review, as well as nutrition status and bad habits are recommended, if at all possible [66]. Several studies pointed out the utility of biomarkers for preoperative risk prediction in developing postoperative cognitive impairments [67,68]. While there is no strong evidence to promote measuring of an extensive panel of inflammatory markers to predict early or long-term cognitive disorders, there is reasonable data recommending the utility of preoperatively CRP (C-reactive protein) levels in patients' risk stratification to develop postoperative delirium [69][70][71].…”
Section: Current Anesthetic Strategies For Preventing Postoperative D...mentioning
confidence: 99%